2012
DOI: 10.1097/sa.0b013e318269d3d4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Isoflurane and Desflurane on Cognitive Function in Humans

Abstract: BACKGROUND:The etiology of postoperative cognitive decline (POCD) remains to be determined. Anesthetic isoflurane, but not desflurane, may induce neurotoxicity. However, the functional consequences of these effects have not been assessed. We therefore performed a pilot study to determine the effects of isoflurane and desflurane on cognitive function in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Isoflurane, one of the most widely used inhalational anaesthetics, is extensively used beyond surgical interventions, including painless induced delivery or endoscopy. Previously, results from our lab and other studies demonstrated that cognitive functions were significantly impaired following isoflurane anaesthesia in both human and mice (Zhang B et al 2012;Xia et al 2016;Fang et al 2017;Ni et al 2017;Zuo et al 2018). It has also been reported that isoflurane causes severe oxidative stress by impairing antioxidant enzymes, inducing mitochondrial dysfunction and increasing the levels of ROS .…”
Section: Discussionmentioning
confidence: 62%
“…Isoflurane, one of the most widely used inhalational anaesthetics, is extensively used beyond surgical interventions, including painless induced delivery or endoscopy. Previously, results from our lab and other studies demonstrated that cognitive functions were significantly impaired following isoflurane anaesthesia in both human and mice (Zhang B et al 2012;Xia et al 2016;Fang et al 2017;Ni et al 2017;Zuo et al 2018). It has also been reported that isoflurane causes severe oxidative stress by impairing antioxidant enzymes, inducing mitochondrial dysfunction and increasing the levels of ROS .…”
Section: Discussionmentioning
confidence: 62%
“…The mPTP opening blocker CsA can mitigate the isoflurane‐induced impairment of learning and memory. These results, together with findings that desflurane anesthesia may lead to a lesser degree of cognitive decline in humans than isoflurance anesthesia,36 suggest that desflurane could be a better choice of anesthetic than isoflurane for AD patients who are susceptible to development of cognitive function decline, pending further human studies. Furthermore, these findings suggest that mitochondrial function (eg, opening of mPTP) could be among the molecular mechanisms responsible for different effects of isoflurane and desflurane on function of learning and memory.…”
Section: Discussionmentioning
confidence: 96%
“…For example, some studies suggest that deep anaesthesia (as determined using bispectral index monitoring) is associated with higher incidence of POCD 58 whereas others suggest no association between the depth of anaesthesia and POCD. 59 A pilot study by Zhang and colleagues 60 suggested that perhaps isoflurane might be more likely to cause POCD when compared with desflurane although large-scale studies would be necessary to confirm this notion.…”
Section: Anaesthesia-induced Neurotoxicity and Neuroplasticity In Thementioning
confidence: 99%
“…19 82 Although the clinical relevance of these differences between isoflurane and desflurane remains to be determined, a pilot human study suggests that surgery under anaesthesia with isoflurane, but not desflurane, can lead to cognitive dysfunction in patients. 60 Protection for cognitive dysfunction by overexpression of heat-shock protein 72…”
Section: Agent-specific Differences In Neurotoxicitymentioning
confidence: 99%